QAS 2023
DOI: 10.47750/qas/24.192.28
|View full text |Cite
|
Sign up to set email alerts
|

Indonesia's successful women entrepreneurs: Servant leadership, E-Commerce Digitalization Adoption, self efficacy as Mediation and Adoption of E-Commerce Digitization as Moderatio

Abstract: This study examines the influence of self-efficacy and innovative behavior on successful women entrepreneurs, while also considering the mediating role of self-efficacy and moderating role of e-commerce digitization. This type of research is a survey that uses female SME entrepreneurs as respondents in three provinces in Indonesia, namely West Java, Yogyakarta and Jakarta. The sampling technique used is purposive with a sample size of 234 respondents, and collected the data by distributing questionnaires to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…While the figure appears to be inspiring, the articles that particularly focused on microfinancing for woman-owned enterprises were limited [23,24,54,56,58,81]. Even though the results give the idea that microfinancing has attracted significant interest from scholars across the globe, several of these studies were conducted from emerging countries outside Africa.…”
Section: Conclusion and Future Research Agendamentioning
confidence: 99%
“…While the figure appears to be inspiring, the articles that particularly focused on microfinancing for woman-owned enterprises were limited [23,24,54,56,58,81]. Even though the results give the idea that microfinancing has attracted significant interest from scholars across the globe, several of these studies were conducted from emerging countries outside Africa.…”
Section: Conclusion and Future Research Agendamentioning
confidence: 99%
“…Therefore the role of leadership in entrepreneurial attitudes urgently needs to enhance. The previous report also revealed that servant leadership's a significant positive impact on Indonesia's Successful Women Entrepreneur (Setyaningrum & Muafi, 2023).…”
mentioning
confidence: 93%